O mundo do trabalho no contexto da proposta curricular paulista - Silva, José Humberto da (2012)
The goal of this dissertation is the study of Curriculum Proposal implemented in the network of basic education in the State of São Paulo by the Ministry of Education since 2008. This Curriculum Proposal is part of a larger project entitled School of São Paulo. From 2010, the Curriculum Proposal was named Official Curriculum. Through the analysis of texts that substantiate the Curriculum Proposal we try to understand which the conception of the world of job is presented to high school students. Our research hypothesis is that the understanding that the Department of Education has about the world of job, embodied in the text of the Proposed Curriculum, which is common to all subjects in the curriculum, is its reduction to employment, as a necessary way to maintain the survival and reproduction of the worker. This research has the documental and bibliographic character. We use the documents produced by the Education Department, specifically the text that underlies the Curriculum Proposal. From this analysis, we can state that the Department of Education of São Paulo intended, with the development of the Curriculum Proposal, unify and adjust the methodology of teaching and learning to the goals set by the global education reform for the twenty-first century; intensify control over curriculum and assessment processes; disseminate more intensely pedagogy skills, using a more explicit way to displacing the focus of teaching to the learning, and disseminate an understanding of the world of job reduced to employment, abstracting thus important issues surrounding the debate on labor in contemporary society.